Current status of an issue regarding disorders in the adaptation of servicemen of armed forces of Ukraine, discharged in the result of army reformation - Сукачова, Ольга Миколаївна (Psychological Counseling and Psychotherapy)
Data on the prevalence, structure, clinic, dynamics and outcomes of adaptation disorders in conditions of military service, and after it, at present have been studied not enough. This study was aimed to diagnose adaptation disorders of military personnel discharged from the Armed Forces of Ukraine in the result of army reformation. The frequency of people with and without the signs of adaptation disorders was investigated. Gender and age characteristics of soldiers among groups and subgroups were described. Comparative characteristics of groups and subgroups according to the parameters "education", "employment", "level of financial security", as well as generalized characteristics of marital status of ex-servicemen in the groups were given. As a result of the study, an analysis of the general characteristics of the surveyed soldiers with and without symptoms of adaptation disorder revealed the homogeneity of the most of main indicators, which became the basis for the conclusion about homogeneity of the control and experimental groups and relevance of the data and the representativeness of the study results.